173. Dosimetrical evaluation of interplay effect for lung cancer treatments with Vero system: Comparison between three different techniques. (December 2018) - Comi, S.; Bazani, A.; Emiro, F.; Piperno, G.; Baldini, F.; Jereczek-Fossa, B.A.; Cattani, F.
Abstract: Purpose: To evaluate interplay effect on delivered dose distributions for lung cancer treatments using treatment techniques (DynamicWaveArc[1, 2], DynamicConformalArc and DynamicTumorTracking) performed with VERO system. Methods: For each patient with lung nodules selected for stereotactic treatments a 4DCT with RPM Varian System was acquired. Internal Target Volume (ITV) was created on maximum intensity projection reconstructed from a dataset of ten phases and enlarged to PTV (5 mm margins). For each plan an extreme hypo-IGRT schedule was applied (36 Gy/3fz) with a prescription of D95% PTV = 100%. DWA planning was performed with Collapsed Cone Convolution Superposition on Raystation (v.6.1.1.2) (2 full arcs, GenericX1 template), while DCA and DTT with Monte Carlo algorithm on iPlannet RT Dose (v.4.5.4) (1 full arc and 5 conformal beams, respectively). Plans were recalculated as pre-treatment QA and delivered on BrainLab Respiratory Gating Phantom, applying real patients' breathing patterns. Dose maps were acquired with EBT3 Gafchromic, applying a single scan protocol for absolute dose measurements[3, 4] . All films were read with an EPSON XL10000 scanner in transmission mode (48-bit RGB and 72 dpi resolution) and analyzed with FilmQAPro® 2016 (Ashland). For each technique, absolute dose γ analysis was performed between static and moving delivery, applying 2%-2 mm criteria and no dose threshold. Evaluations were performed considering single and 3-fractions schedule and a mean γ passing rate for 5 patients. Results: Results obtained from analysis of all treatment techniques and both schedules are reported in Table 1. Conclusions: From preliminary studies, the interplay effect is more pronounced in DWA treatments than in other cases, as expected. However as the number of fractions is increased, the γ passing rates become almost acceptable also for DWA. We also started to investigate the interplay effect varying patients' breathing patterns[5] . Results suggest using this technique for moving targets could lead to better OARs sparing.